1999
DOI: 10.5032/jae.1999.04020
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions Of Extension Agents' Educational Needs Regarding Sustainable Agriculture In The Khorasan Province, Iran

Abstract: As Iran addresses its goal of self-sufficiency in the production of food and fiber products, sustainable agriculture practices are gaining interest within Extension and the Ministry of Agriculture as a means of achieving this goal. Dependence on pesticide and insecticide imports, compounded by a growing population, limited arable land and high soil erosion, has lead to the call for more appropriate agricultural practices. Little is known, however, about what knowledge and educational needs Extension agents hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 10 publications
3
10
0
1
Order By: Relevance
“…A gap between what and how information is being offered and what and how farmers wish to receive information exists. Numerous studies have identified to desire of Iranian farmers to be more involved in agriculturally based training and development programs (Chizari, Lindner, & Noorbadi, 2000;Chizari, Lindner, & Zoghie, 1999;Chizari, Karbasioun, & Lindner, 1998). A continued and sustained effort is needed to ensure participatory approaches to education and training are achieved.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A gap between what and how information is being offered and what and how farmers wish to receive information exists. Numerous studies have identified to desire of Iranian farmers to be more involved in agriculturally based training and development programs (Chizari, Lindner, & Noorbadi, 2000;Chizari, Lindner, & Zoghie, 1999;Chizari, Karbasioun, & Lindner, 1998). A continued and sustained effort is needed to ensure participatory approaches to education and training are achieved.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Extension agents in Iran have an important role in helping farmers conserve, protect, rehabilitate, and manage their land, water, and other natural resources (Chizari, Lindner, & Zoghie, 1999). These authors further not that because conservation and sustainable agriculture practices require farmers to spend more time planning, thinking, and developing a strategy for managing farming systems to attain a sustainable agriculture production-farming unit, the majority of farmers in Iran are rejecting recommended practices.…”
Section: Introductionmentioning
confidence: 99%
“…However, the diversity in personal beliefs and value systems of individual extension educators may potentially define individual convictions, perceptions, attitudes and behaviors (Schauber 2001). The importance of perceptions in relation to attitudes towards major agricultural issues is reflected by the number of studies that have been conducted globally in agricultural education (Blezek and Dillon 1991;Bruening, Radhakrishna and Rollins 1992;Chizari, Lindner and Zoghie 1999;Farouque and Takeya 2007).…”
Section: The Theoretical and Conceptual Frameworkmentioning
confidence: 99%
“…Knowledge and related information, skills, technologies and attitudes will play a key role in the sustainable agriculture [38] . Consequently, sustainable agriculture system is an information-intensive system [16] because inputs have been replaced by skills, labors and management [7,8,21,25,29] . For example, in order for farmers that practice sustainable agriculture to be successful in managing their farmlands, there must be a continuous network of information, new technologies and innovations that are available to them.…”
Section: Introductionmentioning
confidence: 99%